Pendampingan Belajar Rumus Pythagoras Menggunakan Kertas Warna pada Siswa SMP Kelas 8 Nurul Jadid - Olief Ilmandira Ratu Farisi; Ulfatun Nazihah; Khusnul Hotimah; Roisah Annuriah Khalila; Devi Linda Ayu Safitri; Eviana Febrianti (Jurnal Pengabdian Pada Masyarakat, 2021)
LEARNING ASSISTANCE FOR PYTHAGOREAN FORMULAS USING COLORED PAPER FOR NURUL JADID MİDDLE SCHOOL STUDENTS. The pandemic caused limited teaching and learning activities in schools, including for the eighth grade students of Nurul Jadid Islamic Boarding School. To help them in understanding the Pythagorean formula, it is proposed learning assistance in this community service. So far, students only know the Pythagorean formula without knowing the proof. Therefore, through this learning assistance, the students be able to construct the Pythagorean formula with two geometric proofs independently using colored paper media. In the implementation of this community service, all students succeeded in putting together the triangles, filliing the greatest square by using the pieces of smaller squares, construct Pythagorean formula based on the arrangement of the triangles and squares, and mention the formula. In addition, the use of colored paper as a learning media makes the learning atmosphere more effective and fun.